Saberes em rede: tecnologia social na Mata Escura - LIMA, Danúbia Leal (2012)
The comprehension about how the Social Technologies Development Laboratory (LTECS) of Salvador University, between 2005 and 2010, applied Social Technology in Mata Escura’s community is the object of study of the actual dissertation. The performance of a Research Group in Salvador’s suburb over 5 years resulted in research, articulation and knowledge in network, which systematized in this study provide the understanding of how Social Technologies can be applied in the urban space, considering scientific knowledge and narrative knowledge as complementary knowledge in the process. The concepts of Non-Formal Education, Identity and Citizenship are elucidated, seeing that these, along the concept of Social Technology, are the knowledge in Network which characterize LTECS’s acting. For the development of this research, the utilized methodology was case study, with direct observation and application of research instruments.